1992
DOI: 10.1034/j.1600-0889.1992.t01-4-00004.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in aerosol size- and phase distributions due to physical and chemical processes in fog

Abstract: Measurements of the scavenging efficiency of aerosol particles in fog are presented. The scavenging efficiency as a function of size for accumulation‐mode particles is presented, along with efficiencies for the total number, accumulation‐mode number, and accumulation‐mode volume. Particles below ca. 0.3 µm diameter were not efficiently scavenged in the fogs. The scavenging efficiency for accumulation‐mode particles showed two steps, indicating that the hygroscopic/hydrophobic nature of the aerosol appeared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 0 publications
6
29
2
Order By: Relevance
“…For the polluted case corresponding to 16-17 July 1997 we found that the majority of the residual particles measured in the Sc clouds with the CVI were larger than 0.1 ¹m in diameter. This is consistent with residual particle size distributions observed in polluted Sc clouds over the North Sea on 9 March 1997 and scavenging ef ciencies in polluted fogs over a continental area (Noone et al 1992). Furthermore, for all cases marked in bold and corresponding to the clean category shown in the table a linear correlation coef cient .r/ of 0.96 is obtained between N aer amp and SF Namp .…”
Section: (C) Observed Cloud Droplet Distributions In Sc and Cu Cloudssupporting
confidence: 86%
See 2 more Smart Citations
“…For the polluted case corresponding to 16-17 July 1997 we found that the majority of the residual particles measured in the Sc clouds with the CVI were larger than 0.1 ¹m in diameter. This is consistent with residual particle size distributions observed in polluted Sc clouds over the North Sea on 9 March 1997 and scavenging ef ciencies in polluted fogs over a continental area (Noone et al 1992). Furthermore, for all cases marked in bold and corresponding to the clean category shown in the table a linear correlation coef cient .r/ of 0.96 is obtained between N aer amp and SF Namp .…”
Section: (C) Observed Cloud Droplet Distributions In Sc and Cu Cloudssupporting
confidence: 86%
“…Glantz and Noone (2000) suggest that as the level of pollution increases in the layer in which clouds form, larger particles can become suf ciently abundant to account for the majority of the cloud droplets formed. For highly polluted conditions Noone et al (1992), using a CVI, observed AMP number-and volumescavenging fractions as low as 1-10% and 20-30%, respectively, in fogs. They also found that particles smaller than 0.3 ¹m diameter were not ef ciently scavenged in the polluted fogs.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Several investigators (Tucker, 1989;Noone et al, 1991Noone et al, , 1992bOgren et al, 1992) have deployed miniaturized, landbased CVIs similar to the one discussed here. These have proven to be useful field instruments; however, they have yet to be carefully calibrated, especially with regard to the minimum cut size and the cut sharpness.…”
Section: Introductionmentioning
confidence: 99%
“…The stable conditions lead to the trapping of pollutants and aerosol particles in the lower layers. This indicates that under the stable, cold and sub-saturated conditions (humidity greater than 80%), initiation of aerosol hydration (not full activation in fog droplets) as haze particles and, to a lesser extent, activation of aerosols in fog droplets 30,31 , might have occurred resulting in quasi-fog/haze conditions following the dense fog. These observations show the complexity of the role of aerosols, suggesting that different processes are at play during various phases of the fog event.…”
Section: Key Processes Involved During Fog Event: 21-25 January 2016mentioning
confidence: 99%